Social Capital and Health: Evidence That Ancestral Trust Promotes Health among Children of Immigrants - Martin Ljunge (Research Institute of Industrial Economics (IFN), 2014)
This paper presents evidence that generalized trust promotes health. Children of immigrants in a broad set of European countries with ancestry from across the world are studied. Individuals are examined within country of residence using variation in trust across countries of ancestry. There is a significant positive estimate of ancestral trust in explaining selfassessed health. The finding is robust to accounting for individual, parental, and extensive ancestral country characteristics. Individuals with higher ancestral trust are also less likely to be hampered by health problems in their daily life, providing evidence of trust influencing real life outcomes. Individuals with high trust feel and act healthier, enabling a more productive life.
Keywords: D13; D83; I12; Z13; 330; Trust; Social capital; Self assessed health; Subjective health; Self reported health; Cultural transmission; Children of immigrants